2017
DOI: 10.1108/ijcma-10-2016-0084
|View full text |Cite
|
Sign up to set email alerts
|

Perceived justice, emotions, and behavioral intentions in the Taiwanese food and beverage industry

Abstract: Purpose The research framework of this study is based on tri-component attitude model (cognition-affect-conation) which explores consumers’ positive or negative emotions, as well as various types of thoughts and actions, triggered by their perceived justice in the context of service failure. This study aims to probe the possible mediating and moderating effects caused by the process where consumers form their thoughts and actions. Design/methodology/approach This study conducts a survey to consumers after re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 107 publications
(161 reference statements)
0
30
1
2
Order By: Relevance
“…MasterCard conducted a survey on consumer spending behavior in 2016 and found that Taiwan ranks fourth in dining-out spending in the Asia Pacific region behind South Korea, Australia, and Singapore [124]. Since the one thing every service can count on is that there is a service failure in the future [3], this study, similar to the research of Ortiz et al (2017), investigates service failure recovery during the dining period regarding restaurant services in Taiwan [13].…”
Section: Design and Samplementioning
confidence: 96%
See 3 more Smart Citations
“…MasterCard conducted a survey on consumer spending behavior in 2016 and found that Taiwan ranks fourth in dining-out spending in the Asia Pacific region behind South Korea, Australia, and Singapore [124]. Since the one thing every service can count on is that there is a service failure in the future [3], this study, similar to the research of Ortiz et al (2017), investigates service failure recovery during the dining period regarding restaurant services in Taiwan [13].…”
Section: Design and Samplementioning
confidence: 96%
“…For example, Alamri et al [22] showed that corneal polymodal nociceptors have TRPV1-positive small ramifying nerve endings, whereas the cold thermoreceptor has TRPM8-positive large complex endings. TRPV1 has also been detected in human corneal epithelial and conjunctival cells [13,23]. Generally, it is known that TRPV1 plays a role in DED, since it can be activated by hypertonic challenge, which in turn leads to an increased release of pro-inflammatory cytokines [24,25].…”
Section: Trp Channels Related To Ocular Pain In Dedmentioning
confidence: 99%
See 2 more Smart Citations
“…It is recognized that service failures trigger negative emotions" (Ortiz et al, 2017) such as anger, regret, disappointment, frustration, shame, guilt, and fear (Laros and Steenkamp, 2005;Sánchez-García and Currás-Pérez, 2011). Such human responses are inconsistent and responses can vary dramatically to near identical failures.…”
Section: Ccbmentioning
confidence: 99%